Global Regulation of Gene Expression by the MafR Protein of Enterococcus faecalis - Ruiz-Cruz, Sofía; Espinosa, Manuel; Goldmann, Oliver; Bravo, Alicia (Frontiers in Microbiology, 2016)
Enterococcus faecalis is a natural inhabitant of the human gastrointestinal tract. However, as an opportunistic pathogen, it is able to colonize other host niches and cause life-threatening infections. Its adaptation to new environments involves global changes in gene expression. The EF3013 gene (here named mafR) of E. faecalis strain V583 encodes a protein (MafR, 482 residues) that has sequence similarity to global response regulators of the Mga/AtxA family. The enterococcal OG1RF genome also encodes the MafR protein (gene OG1RF_12293). In this work, we have identified the promoter of the mafR gene using several in vivo approaches. Moreover, we show that MafR influences positively the transcription of many genes on a genome-wide scale. The most significant target genes encode components of PTS-type membrane transporters, components of ABC-type membrane transporters, and proteins involved in the metabolism of carbon sources. Some of these genes were previously reported to be up-regulated during the growth of E. faecalis in blood and/or in human urine. Furthermore, we show that a mafR deletion mutant strain induces a significant lower degree of inflammation in the peritoneal cavity of mice, suggesting that enterococcal cells deficient in MafR are less virulent. Our work indicates that MafR is a global transcriptional regulator. It might facilitate the adaptation of E. faecalis to particular host niches and, therefore, contribute to its potential virulence.